AMALAN QUDWAH HASANAH KEPIMPINAN ISLAM PENGETUA : THE PRACTICE OF QUDWAH HASANAH IN THE ISLAMIC LEADERSHIP OF PRINCIPAL - Othman, Rashidah; Md Nawi, Noor Hisham (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
Kajian ini bertujuan mengenalpasti amalan qudwah hasanah dalam kepimpinan Islam pengetua. Kepimpinan Islam berteraskan qudwah hasanah atau teladan merupakan asas penting dan menuntut pengetua bukan sahaja berperanan sebagai pengurus organisasi tetapi juga sebagai teladan untuk akhlak dan nilai Islam. Namun begitu, sebahagian pengetua tidak dapat menzahirkan kepimpinan berasaskan qudwah hasanah secara konsisten. Objektif kajian ialah mengenalpasti amalan qudwah hasanah yang diamalkan oleh pengetua. Metodologi kajian ini menggunakan pendekatan kajian kepustakaan dengan menganalisis dokumen dan meneliti artikel berkaitan. Dapatan analisis menunjukkan bahawa amalan pengetua merangkumi sifat keikhlasan, adil, kasih sayang, musyawarah dan budaya organisasi memberi kesan positif yang mampu membentuk budaya organisasi cemerlang dan meningkatkan motivasi guru. Kajian ini akan menyumbang kepada pembangunan ilmu kepimpinan Islam yang relevan dengan cabaran semasa, memberi panduan kepada pengetua dan penggubal dasar dalam memperkukuh kepimpinan berasaskan qudwah hasanah sekaligus mengisi jurang kajian dimensi praktikal qudwah hasanah dalam kepimpinan Islam. This study aims to identify the practices of Qudwah Hasanah in the Islamic leadership of school principals. Islamic leadership based on Qudwah Hasanah, or exemplary conduct, is an essential foundation that requires principals not only to function as organisational managers but also to serve as role models in embodying Islamic morals and values. However, some principals are unable to consistently demonstrate leadership grounded in Qudwah Hasanah. The objective of this study is to identify the Qudwah Hasanah practices adopted by school principals. This study employs a literature review approach by analysing documents and examining related scholarly articles. The findings indicate that the practices of principals include sincerity, justice, compassion, consultation (musyawarah), and the cultivation of a positive organisational culture and enhancing teachers’ motivation. This study contributes to the development of Islamic leadership knowledge that is relevant to contemporary challenges and provides guidance for principals and policymakers in strengthening leadership based on Qudwah Hasanah. At the same time, it helps to fill the research gap regarding the practical dimensions of Qudwah Hasanah in Islamic leadership.